Accuracy of Mandible-First versus Maxilla-First Approach and of Thick versus Thin Splints for Skeletal Position after Two-Jaw Orthognathic Surgery. Issue 2 (24th November 2020) - Borikanphanitphaisan, Thatchawee; Lin, Cheng-Hui; Chen, Ying-An; Ko, Ellen Wen-Ching
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The aim of this study was to investigate the accuracy of bimaxillary orthognathic surgery regarding different sequencing (maxilla-first or mandible-first surgery) and different thicknesses of intermediate splints. Methods: This retrospective cohort study evaluated the accuracy of postoperative outcome in accordance with virtual planning in 57 patients requiring bimaxillary osteotomies with different operation sequence: maxilla-first ( n = 31) or mandible-first ( n = 26) surgery. The effect of different splint thicknesses (i.e., thick, n = 22; and thin, n = 35) was also evaluated. The 1-week postoperative cone-beam computed tomographic craniofacial images were superimposed onto preoperative simulated images to measure the discrepancy of the three-dimensional cephalometric landmarks. Results: Neither sequencing approach differed in overall accuracy (1-week postoperative to preoperative simulated image discrepancy): maxilla-first, 1.69 ± 0.53 mm; versus mandible-first, 1.44 ± 0.52 mm. In detailed comparison, mandible-first surgery resulted in more accuracy in the vertical dimension. Thick intermediate splints provided better control (less error) of upper central incisors in the sagittal position (thick splint, 1.38 ± 1.17 mm; thin splint, 2.13 ± 1.38 mm). However, overall accuracy was not affected by splint thickness. Conditions affecting sequencing predilection included skeletal class III with vertical excess, maxillary down-grafting, counterclockwise rotation of the maxillomandibular complex, and simulated mandibular opening for splint fabrication clearance. Conclusions: Despite both means of sequencing being performed similarly, mandible-first surgery was more precise in the vertical dimension. Thick intermediate splints seemed to yield better control of central incisors in the sagittal position. However, under appropriate selection of intermediate splints to maintain interim condylar position, splint thickness has no effect on overall accuracy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.